2013
DOI: 10.1177/016264341302800301
|View full text |Cite
|
Sign up to set email alerts
|

Using Electronic Performance Support Systems to Improve Academic Performance of Secondary Students with Disabilities

Abstract: A key challenge in secondary education and transition is ensuring that students with disabilities are prepared to access and participate in postsecondary education. Electronic performance support systems offer potential for addressing needs of secondary students who are at risk for failure or who encounter challenges in school due to high-incidence disabilities. The purpose of this study was to investigate the effects of training and implementation of an electronic performance support systems on targeted IEP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…The grant resulted in one published single-case study. In this study, Mitchem, Fitzgerald, Miller, and Hollingsead (2013) demonstrated a functional relation between using Strategy Tools Support System and note-taking and writing from a prompt with ninth- and 12th-grade participants with high-incidence disabilities. Teachers reported the tools were acceptable and requested schoolwide training on how to use the tools.…”
Section: Resultsmentioning
confidence: 69%
“…The grant resulted in one published single-case study. In this study, Mitchem, Fitzgerald, Miller, and Hollingsead (2013) demonstrated a functional relation between using Strategy Tools Support System and note-taking and writing from a prompt with ninth- and 12th-grade participants with high-incidence disabilities. Teachers reported the tools were acceptable and requested schoolwide training on how to use the tools.…”
Section: Resultsmentioning
confidence: 69%
“…While some of the researches that were conducted on EPSS focussed on what an EPSS needed to possess, 26–28 some others gave attention to the effect of the system developed within the framework of the study in question on users 29–33 . In the present study, an EPSS was developed taking the literature as a basis and considering the opinions of users and experts.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason of positive research result may be the fact that the students did not have any technical problems while getting access to the system and using it because it was found out that the technical problems that arose decreased the satisfaction with EPSS and the frequency of its usage 28,30 . It has been concluded in many researches that EPSSs that ensure users to avoid problems and to have a quick access to knowledge improve academic achievement and performance 26,28,30,33 . On the other hand, Kalota and Hung (2013) 29 found out conflicting results regarding that EPSSs had no effect on improving learning.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Alparslan, 2009;Bollen et al, 2015;Chen et al, 2009;Kalota & Hung, 2013b;Kert et al, 2014;Li & Peng, 2016;Lizdas et al, 2017;Martinez-Mediano & Losada, 2017;Mitchell, 2014;Mitchem et al, 2013) used advanced programming technologies to develop an EPSS. In this study, the focus was on the development of a mid-level EPSS based on the ED4 model and providing interaction by integrating Moodle, while paying attention to recommendations in the literature concerning desirable EPSS features.…”
Section: Discussionmentioning
confidence: 99%
“…An EPSS must have these four components, however, the relevant literature also identifies the following situations that need to be taken into account when developing an EPSS. : a simple design (Askar, 2018;Barker et al, 2007;Bollen et al, 2015;Carvalho, 2018;Chen et al, 2009;Kalota & Hung, 2013b); brief subject-specific information (Barker et al, 2007;Bollen et al, 2015;Klein & Reiser, 2014;Martinez-Mediano & Losada, 2017); development on the basis of target audience analysis (Alparslan, 2009;Bollen et al, 2015;Chen et al, 2009;Kalota & Hung, 2013b); ease of updating (Bollen et al, 2015); development in the form of modular information structures (Bollen et al, 2015;Martinez-Mediano & Losada, 2017); provision of step-by-step task instructions (Li & Peng, 2016;Mitchell, 2014); use in real world job environments (Alparslan, 2009;Chen et al, 2009;Li & Peng, 2016;Martinez-Mediano & Losada, 2017;Mitchell, 2014); integration with learning management systems (Bollen et al, 2015;Dias et al, 2017;Martinez-Mediano & Losada, 2017;Mitchell, 2014); and interaction with other sources of information (Bollen et al, 2015;Chen et al, 2009;Mitchem et al, 2013;Ugur-Erdogmus & Cagiltay, 2018).…”
Section: Developing and Investigating An Electronic Performance Support System (Epss) For Academic Performance Introductionmentioning
confidence: 99%